Antarctic heavy metal pollution and remediation efforts: state of the art of research and scientific publications - Darham, Syazani; Zakaria, Nur Nadhirah; Zulkharnain, Azham; Sabri, Suriana; Khalil, Khalilah Abdul; Merican, Faradina; Gomez-Fuentes, Claudio; Lim, Sooa; Ahmad, Siti Aqlima (Institute for Ionics, 2023)
In Antarctica, human activities have been reported to be the major cause of the accumulation of heavy metal contaminants. A comprehensive bibliometric analysis of publications on heavy metal contamination in Antarctica from year 2000 to 2020 was performed to obtain an overview of the current landscape in this line of research. A total of 106 documents were obtained from Scopus, the largest citation database. Extracted data were analysed, and VOSviewer software was used to visualise trends. The result showed an increase in publications and citations in the past 20 years indicating the rising interest on heavy metal contamination in the Antarctic region. Based on the analysis of keywords, the publications largely discuss various types of heavy metals found in the Antarctic water and sediment. The analysis on subject areas detects multiple disciplines involved, wherein the environmental science was well-represented. The top countries and authors producing the most publication in this feld were from Australia, China, Brazil and Chile. Numerous eforts have been exercised to investigate heavy metal pollution and its mitigation approaches in the region in the past decades. This paper not only is relevant for scholars to understand the development status and trends in this feld but also ofers clear insights on the future direction of Antarctic heavy metal contamination and remediation research.